ANALISIS KEUNTUNGAN USAHA CV. INDOSPICE DI TUMINTING KOTA MANADO - Tri Mirta Dewi; Paulus A. Pangemanan; Ribka M. Kumaat (AGRI-SOSIOEKONOMI, 2018)
This study aims to analysis the profit received by CV. Indospice in one month production process. The study was conducted in January to March 2017. Located at CV. Indospice in Tuminting, Manado City. This research uses primary data and secondary data. The data used in this study using tables that are then described and analysis using profit analysis. The profit was obtained by the difference between revenue and cost incurred. The results showed that CV. Indospice in Tuminting, Manado City get a profit of Rp. 153,618,396 per month at a cost of Rp. 748.381.604 and the value of R / C cost revenue of 1.29 which means CV. Indospice gained profit.*jnkd*.